Adaptive Contents Distribution Based on Traffic Congestion on Digital Signage System - Alifudin, Ridhwan; Rakhmatsyah, Andrian; Yasirandi, Rahmat (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2019)
Current technological developments have been very rapid. One of them is the many choices of technology and media to deliver information to the public. Digital Signage is one of the most popular information delivery systems today, displays on digital or electronic media, and it can convey new details. The information usually showed in the form of advertising content in the format of images or videos. Ad content displayed is static, meaning that the ad content will be display in the order specified. This system usually placed next to a broad road. A place that is considered to have a broad audience and requires a significant amount of money to display ad content. However, this causes ad content owners who do not have enough costs not to be able to show the ad content in a particular place. Therefore, this research makes the content management system adaptive to road congestion situations which represented as audience quantities so that the costs can be adjusted. Data is obtained from the Google Maps API and analyzed the traffic congestion by conducting experiments. The compatibility between density and content after testing the results in 100% accuracy.